Picking Bananas, Trinidad - (:unkn) unknown (Wilsons Limited, Trinidad, 2009)
A picture of women carrying bunches of bananas on their heads from the fields behind them.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bananas--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Headgear--Trinidad and Tobago; Working class--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Blacks--Trinidad and Tobago; [1915]; Hats--Trinidad and Tobago; Harvesting--Trinidad and Tobago; Exports--Trinidad and Tobago; Banana trade--Trinidad and Tobago